The Role of UIN Alauddin Makassar Library in Supporting MBKM Program - Taufiq Mathar; Hijrana Hijrana; Haruddin Haruddin; A. Khaidir Akbar; Irawati Irawati; Satriani Satriani (International Conference on Social and Islamic Studies, 2021)
Academic libraries play an important role in supporting teaching and learning programs in their institutions. All services that he has provided must adapt to current and future conditions, including the reading materials it prepares. This paper is aimed to describe the role of UIN Alauddin Makassar Library in supporting "Merdeka Belajar Kampus Merdeka" or "Freedom to Learn" program. This qualitative study gathered the data through observation, literature resources, and in-depth interviews. In the university library, the scope of PTKIN through librarians can contribute to the independent campus program and independent learning which directly provides facilities, collections of library materials (printed and electronic) for the academic community in learning as well as through activities designed by the library to strengthen skills and abilities. literacy for students and lecturers. "Freedom to teach for lecturers and freedom to learn for students is a must".